3D spheroid cell cultures and their role in bone regeneration : a systematic review = Cultivos de esferoides 3D y su papel en la regeneración ósea : una revisión sistemática - Cuevas González, María Verónica
Recently, the 3D spheroid cell culture application has been extensively used in the treatment of bone defects. A wide variety of methodologies have been used, which has made the comparison of results complex. Therefore, this systematic review has two aims: (i) to perform an analysis focused on the role of 3D spheroid cell culture in bone regeneration strategies; and (ii) address the main challenges in clinical application. A search of the following keywords "3D cell culture", "spheroid", and "bone regeneration" was carried out in the PubMed, Scopus, and ScienceDirect databases and limited to the years 2010-2020. Studies were included if their primary objective was the behavior of cell aggregates to formed spheroids structures by different 3D cell culture techniques focused on the regeneration of bone tissue. To address the risk of bias for in vitro studies, the United States national toxicology program tool was applied, and descriptive statistics of the data were performed, with the SPSS V.22 program. A total of 16 studies were included, which met the established criteria corresponding to in vitro and in vitro/in vivo studies; most of these studies used stem cells for the 3D cell spheroids. The most often methods used for the 3D formation were low adherence surface and rotational methods, moreover, mesenchymal stem cells were the cell line most frequently used because of their regenerative potential in the field of bone tissue engineering. Although the advances in research on the potential use of 3D spheroids in bone regeneration have made great strides, the constant innovation in cell spheroid formation methodologies means that clinical application remains in the future as strategy for 3D tissue bioprinting.